Comparison of four assays for human papillomavirus detection in the anal canal. (December 2022) - Poynten, I. Mary; Jin, Fengyi; Molano, Monica; Machalek, Dorothy A.; Roberts, Jennifer M.; Hillman, Richard J.; Cornall, Alyssa; Phillips, Samuel; Templeton, David J.; Law, Carmella; Fairley, Christopher K.; Grulich, Andrew E.; et al.
Abstract: Objective: Anal cancer is preceded by high-risk human papillomavirus (HRHPV) infection, predominantly HPV16. No HPV assay is licenced for use in anal screening. We aimed to determine the sensitivity and specificity of four anal canal swab HPV assays to predict high-grade squamous epithelial lesions (HSIL). Methods: In a cohort of Australian HIV-positive and negative gay and bisexual men, we compared the sensitivity and specificity of detection of 13 anal HRHPV genotypes by Linear Array (LA), Cobas 4800, EuroArray, and Anyplex II HPV28 (+ and ++ cut offs), compared their ability to predict prevalent anal HSIL, and compared anal canal HRHPV detection with HRHPV isolated from HSIL using laser capture microdissection (LCM). Results: A total of 475 participants had baseline results available for all four assays (166, 35.0% HIV positive), and 169 participants had a diagnosis of cytological and/or histological HSIL. The HPV16 and any HRHPV detection were highest with Anyplex II HPV28 (+) (156, 32.8% 95% CI 28.6–37.2 and 359, 75.6%, 95% CI 71.5–79.4, respectively). For detection of concurrent HSIL and HPV16, the assay sensitivity was similar, ranging from 49.1%, 95% CI 41.4–56.9 (Anyplex II HPV28 ++) to 55.0%, 95% CI 47.2–62.7 (Anyplex II HPV28 +). For concurrent HSIL and any HRHPV detection, EuroArray was more specific than Anyplex II HPV28 (+) (45.9% 95% CI 40.2–51.7 vs 36.7%, 95% CI 31.3–42.4, p = 0.021) and had comparable specificity with Anyplex II HPV28 (++) (45.9% vs 47.2%, 95% CI 41.5–53.0, p = 0.75). All assays had high sensitivities for predicting HPV16 detected on LCM (92.5–97.5%). Anyplex II HPV28 and EuroArray were significantly more sensitive than LA for lesions caused by non-HPV16 HRHPV types on LCM. Discussion: Anyplex II HPV28 and EuroArray detected more non-16 HRHPV genotypes than LA. Increasing the Anyplex II HPV28 cutoff improved specificity without compromising sensitivity for detection of concurrent HSIL.